Seroprevalence of Japanese encephalitis virus among domestic animals and rats in Mindanao, Philippines - Baltazar, Emmanuel T.; Abella, Jose Alexander C.; Dargantes, Alan P.; Simborio, Luzviminda T.; Bautista, Reu Caesar James T.; Dinopo, Nikko Manuel A.; Ebora, Valeen Drex Bendette M.; Hiroshi Shimoda; Ryusei Kuwata; Eiichi Hondo; Ken Maeda (2022)
The Japanese encephalitis virus (JEV), an arthropod-borne virus chiefly transmitted by mosquitoes, can infect humans, domestic, and wild animal species with usually subclinical manifestation in humans, and animals but can cause acute encephalitis in humans and horses, and reproductive illness in pigs. This serological survey confirmed JEV antibodies in various domestic animals and rats in Mindanao by indirect ELISA with an overall apparent seroprevalence of 12.6% (570/4,525 total samples). Animal species variation was observed, which can be attributed to the differences in behavior and raising management, and feeding behavior of mosquito vectors, and some are amplifying hosts of the virus. Regional variation was also scrutinized, which may be due to differences in vegetation, altitude, and water bodies influencing temperature and humidity that influence feeding behavior and reproduction of mosquito vectors. Results indicate that JEV has been circulating among domestic animals and rats, showing a potential human risk through mosquito bites. Results of this study may widen the understanding of the epidemiology of JEV in Mindanao
Keywords: Encephalitis Viruses; Arboviruses; Epidemics